2021
DOI: 10.3389/fmed.2021.724488
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Preparation Method of Ideal Platelet-Rich Fibrin Matrix From Whole Blood

Abstract: One bioproduct that is widely used in the wound healing process is platelet-rich plasma (PRP). PRP is a liquid solution with high autologous platelet concentration, making it a good source of growth factors to accelerate wound healing. Recent development in PRP had created a new product called platelet-rich fibrin matrix (PRFM), which has a denser and more flexible structure. PRFM is the newest generation of platelet concentrate with a fibrin matrix that holds platelet in it. The key concept in creating PRFM f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Architecturally and nanostructurally interconnected fibrin networks in PRF biomaterials can be visualized using various techniques, such as hematoxylin and eosin staining, atomic force microscopy, confocal laser scanning microscopy, and scanning electron microscopy [40,41]. Scanning electron microscopy (SEM) micrographs of PRF revealed a polymerized interconnected fibrin network and a large population of living cells, including lymphocytes, neutrophils, monocytes, platelets, erythrocytes, and stem cells [39,42]. The PRF fibrin matrix, a natural polymeric three-dimensional network formed after fibrin polymerization, allows for increased entrapment of circulating cytokines and growth factors as well as prolonged release of these molecules into the extracellular matrix [11,43].…”
Section: Discussionmentioning
confidence: 99%
“…Architecturally and nanostructurally interconnected fibrin networks in PRF biomaterials can be visualized using various techniques, such as hematoxylin and eosin staining, atomic force microscopy, confocal laser scanning microscopy, and scanning electron microscopy [40,41]. Scanning electron microscopy (SEM) micrographs of PRF revealed a polymerized interconnected fibrin network and a large population of living cells, including lymphocytes, neutrophils, monocytes, platelets, erythrocytes, and stem cells [39,42]. The PRF fibrin matrix, a natural polymeric three-dimensional network formed after fibrin polymerization, allows for increased entrapment of circulating cytokines and growth factors as well as prolonged release of these molecules into the extracellular matrix [11,43].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the second-generation platelet concentrate (PRF) was developed in France by Choukroun et al in 2001 ( 14 , 15 ). Some studies have shown that platelet-rich fibrin (PRF) increases vascularization by stimulating the production of angiogenesis-related factors (e.g., VEGF, basic fibroblast growth factor, plate- let-derived growth factor, and epidermal growth factor), which leads to new blood vessel formation by modulating the activation, proliferation, and migration of endothelial cells ( 17 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Without any additives, platelets are activated within a few minutes after contacting the walls of the tube, which stimulates the coagulation cascade [6][7][8]. The success of PRF isolation depends on the time taken from the speed of blood collection to the transfer of tubes to the centrifugation machine [9][10][11]. Quick handling of PRF isolation is the best way to obtain a clinically and therapeutic usable L-PRF clot [3,8].…”
Section: Introductionmentioning
confidence: 99%